Scholars Experiencing Epistemic Injustice Due to Management of Scholarly Outputs. Issue 1 (14th October 2022) - Ford, Angela; Alemneh, Daniel
Abstract: Scholars from regions outside of high‐income countries experience additional barriers as active consumers, producers, and sharers of scholarly outputs. This study will examine these barriers through a lens based on critical theories, specifically those focused on epistemic injustice. The findings will highlight the experienced impediments and demonstrate theoretically how disparities can be categorized. The findings will also highlight current publishing paradigms affecting the management of scholarly outputs and at times perpetuating these injustices. Possible future research to support these claims will also be discussed.